Enhancing Student Feedback Efficacy: A Critical Analysis of University's Module Evaluation Questionnaires - Winch, Junko; Demirkol, Sam (Universitas Majalengka, 2024)
This report discusses a British university Module Evaluation Questionnaires (MEQ) which was produced as a part of university-wide interdisciplinary MEQ project at a British University. Purpose: The aim of this report is to investigate the purpose of university MEQ and to review aims and weakness of the current Sussex University MEQ seven questions/statements. Methods: The method is quantitative and critical review and analysis was conducted. Data was collected at University of Sussex, UK. The participants were three members of the MEQ project team. The focus of analysis is to identify the aim and weakens of the current University MEQ questions/statements. Results: MEQ has three stakeholders, students, university and staff. Each stakeholder’s purpose of MEQ are different. University has institutional and teaching staff have teaching and academic promotional purposes. It is suggested to MEQ designers to take consideration of students whose mother tongue is not English and to write questions as simple and clear language as possible. Implications: The primary recommendation of this report is to undertake a staff-student partnership to agree the purpose of the MEQs and co-design a revised instrument that meets the stated purpose.